1996
DOI: 10.1177/096032719601501109
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting hospital admission and length of stay of poisoned patients in the North East of England

Abstract: 1 Poisoning is a common reason for presentation to hospital and hospital admission but there is no agreed policy for managing these patients. This study exam ined the management of patients presenting with poisoning and the factors affecting the probability of hospital admission and prolonged stay. 2 Data on all cases of poisoning presenting to six Accident and Emergency departments in the North East of England over 12 weeks in 1994 was collected prospectively from A&E notes. Len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 13 publications
2
19
1
1
Order By: Relevance
“…In this study, the period of hospitalization was found to be approximately 1.8 days. This period was found as 0.7 days by Özköse et al 6 , 3 days by Lamninpaa et al 38 and 1.5 days by Thomas et al, 39 The hospitalization period in our study is higher than the hospitalization rate found by Özköse and this may be caused by the higher rate of pesticide poisonings in our study. The length of stay can be affected by causes of poisoning such as drugs, pesticides, foods, in addition to the amount of the substance taken and to the non-intentional or intentional character of the poisoning, the latter presentable with more severe outcomes.…”
Section: Discussioncontrasting
confidence: 62%
“…In this study, the period of hospitalization was found to be approximately 1.8 days. This period was found as 0.7 days by Özköse et al 6 , 3 days by Lamninpaa et al 38 and 1.5 days by Thomas et al, 39 The hospitalization period in our study is higher than the hospitalization rate found by Özköse and this may be caused by the higher rate of pesticide poisonings in our study. The length of stay can be affected by causes of poisoning such as drugs, pesticides, foods, in addition to the amount of the substance taken and to the non-intentional or intentional character of the poisoning, the latter presentable with more severe outcomes.…”
Section: Discussioncontrasting
confidence: 62%
“…[13] The clinical course and ultimate outcome, in turn, is related to the agent, the dose, pre-existing comorbidities, the time from exposure to presentation to a healthcare facility and the experience of care provider. [167] However, there is scarcity of data from the Indian subcontinent regarding the epidemiology and outcome of patients presenting with acute poisoning, especially from those patients admitted to ICU. Hence, we aimed to determine the profile and outcome of acute toxicology in patients admitted to ICU of a tertiary care hospital in the cosmopolitan city of New Delhi, India.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] Pharmaceutical agents are more frequently involved in teenager intoxications, whereas nonpharmaceutical agents are more prevalent in younger children. Importantly, the type of agent involved did not change significantly during the study period, and acetaminophen remains the most commonly ingested medication.…”
Section: Commentmentioning
confidence: 99%